One Less Barrier to Alliance: Improving Outcomes of Psychotherapy and Ombuds Practice in Visible Minority Communities - Ismaili, Houda (Université d'Ottawa | University of Ottawa, 2025)
As psychotherapy and ombuds services become more accessible in our societies, some groups are still marginalised. Research shows that visible minorities are much less likely to report a positive outcome or even continue seeking these services after one session. Research shows that one of the main reasons for this unfortunate reality is the lack of alliance that visible minorities feel, especially when their service providers are non-minorities. Finally, research shows that a strong alliance is key to retention and positive outcomes. The current research aims to study the EASE model in psychotherapy and ombuds services; a model that emphasises empathetic listening, acknowledgement of circumstances, solving (through sensible action) and evaluating (through exploration of thoughts) (EASE). Perceived use of EASE skills in services as usual was explored in relation to alliance, mental health, and other outcomes. In study 1, the psychotherapy sample consisted of 53 participants, 28 of whom were visible minorities and 25 non-minorities; nine participants had seen psychotherapists who were visible minorities while 33 participants had seen psychotherapists who were non-minorities. In study 2, the ombuds service sample consisted of 14 participants, six of whom were visible minorities and three who were not visible minorities: three participants had seen ombuds who were visible minorities, and six participants had seen ombuds who were non-minorities. These studies used a knowledge translation integrated (KTI) and mixed methods approach. These studies included measures of alliance, EASE, Meaning Mindset, mental health, and client-rated therapist multicultural competence. The hypothesis was that participants, clients or visitors, who had worked with service providers whom they perceived to have used EASE skills would score higher on these measures, and would be more likely to complete services, rather than terminate prematurely. This research used a KTI approach to collaborate with visible minorities to improve their experience in psychotherapy and ombuds services so that they are more likely to benefit from them. This thesis is an article format thesis. The first chapter introduces psychotherapy and ombuds services with relation to the variables relevant to the current research. The second chapter is an article on study 1, concerning the psychotherapy client population. The third chapter is an article on study 2, concerning the ombuds visitor population. The fourth chapter is an overarching discussion.
Keywords: psychotherapy; ombuds; visible minority; alliance; retention rate; mental health